2016
DOI: 10.1093/mnras/stw288
|View full text |Cite
|
Sign up to set email alerts
|

Optical intensity interferometry through atmospheric turbulence

Abstract: Conventional ground-based astronomical observations suffer from image distortion due to atmospheric turbulence. This can be minimized by choosing suitable geographic locations or adaptive optical techniques, and avoided altogether by using orbital platforms outside the atmosphere. One of the promises of optical intensity interferometry is its independence from atmospherically induced phase fluctuations. By performing narrowband spectral filtering on sunlight and conducting temporal intensity interferometry usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…The filtered light is polarized by a first polarizing beam splitter (PBS), and distributed by a second PBS into a pair of actively quenched Silicon avalanche photodetectors (APD) with a timing jitter of about 40 ps (Tan et al 2016). Photodetection rates are balanced by rotating the first PBS which is preceeded by a half wave plate to maximize the count rates.…”
Section: Methodsmentioning
confidence: 99%
“…The filtered light is polarized by a first polarizing beam splitter (PBS), and distributed by a second PBS into a pair of actively quenched Silicon avalanche photodetectors (APD) with a timing jitter of about 40 ps (Tan et al 2016). Photodetection rates are balanced by rotating the first PBS which is preceeded by a half wave plate to maximize the count rates.…”
Section: Methodsmentioning
confidence: 99%
“…After some preparatory experimental activities carried out by some groups (Zampieri et al 2016;Tan, Chan, & Kurtsiefer 2016;Matthews et al 2018;Weiss, Rupert, & Horch 2018), new successful stellar intensity interferometry (SII) measurements a là Hanbury Brown and Twiss have recently been realized using the particle nature of light and modern fast single-photon counters. The first intensity ★ E-mail: luca.zampieri@inaf.it correlation measured with starlight from conventional optical telescopes since the historical experiments of Hanbury Brown and Twiss has been performed by Guerin et al (2017), and more recently by Rivet et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dravins et al (2015) observed pinholes illuminated by scattered laser light in the laboratory and demonstrated that the image of a source can be reconstructed from | ( , )| 2 if the plane is densely sampled. Tan et al (2016) measured the temporal coherence function (intensity autocorrelation) | ( = 0, = 0, )| 2 , with being a time delay, of sunlight. Guerin et al (2017) measured the intensity autocorrelations in the light from three stars.…”
Section: Introductionmentioning
confidence: 99%